2018
DOI: 10.1371/journal.pone.0190654
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood cell microRNA quantification during the first trimester predicts preeclampsia: Proof of concept

Abstract: ObjectiveWe investigated the capacity of microRNAs isolated from peripheral blood buffy coat collected late during the first trimester to predict preeclampsia.Study designThe cohort study comprised 48 pregnant women with the following pregnancy outcomes: 8 preeclampsia and 40 with normal delivery outcomes. Quantitative rtPCR was performed on a panel of 30 microRNAs from buffy coat samples drawn at a mean of 12.7±0.5 weeks gestation. MicroRNA Risk Scores were calculated and AUC-ROC calculations derived.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
(40 reference statements)
1
24
0
Order By: Relevance
“…The results of the current research are consistent with previous studies published by our group that have demonstrated that peripheral blood cell microRNA obtained during the first trimester of pregnancy predicts risk of preterm delivery [34], spontaneous abortion [37,33], and preeclampsia [32]. In addition, the current study confirms the usefulness of peripheral blood cell microRNA as biomarkers identifying risk of preterm birth early in the first trimester.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the current research are consistent with previous studies published by our group that have demonstrated that peripheral blood cell microRNA obtained during the first trimester of pregnancy predicts risk of preterm delivery [34], spontaneous abortion [37,33], and preeclampsia [32]. In addition, the current study confirms the usefulness of peripheral blood cell microRNA as biomarkers identifying risk of preterm birth early in the first trimester.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 92%
“…Winger and Reed suggested an alternative to interrogation of plasma components. They hypothesized that interrogation of the maternal immune cell component of the placental bed would offer at least two significant advantages: first, the method would eliminate the interrogation of an intermediary organ, the placenta, rather than direct interrogation of the underlying pathology in the placental bed and, second, the method would allow recognition of the underlying pathology at an earlier time point [ 32 34 , 37 ]. However, investigation of the placental bed is more challenging than examination of placental shed components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess the possibility of prediction of preeclampsia by analyzing microRNAs from peripheral blood buffy coat samples of pregnant women, Winger and coauthors investigated 30 microRNAs (43). Authors performed qRT-PCR analysis on samples of 48 pregnant women collected during first trimester of pregnancy (11±13 weeks gestation), of whom 8 had preeclampsia.…”
Section: Role Of Micro-rna In Preeclampsiamentioning
confidence: 99%